PERAN CORPORATE COMMUNICATIONS DALAM MEMBANGUN CITRA PERUSAHAAN TERHADAP STAKEHOLDER PT HUTAMA KARYA INFRASTRUKTUR - Nadya Maulida Larissa, (2022)
PT Hutama Karya Infrastruktur is a subsidiary of a State-Owned Enterprise (BUMN) which is working on one of the longest toll road projects in Indonesia, namely the Sumatra Toll Road. ensuring that the company has an obligation to build a company image that is seen as good by external stakeholders. The role of Corporate Communication or company public relations is certainly very important in building this good reputation. The research method used is descriptive qualitative with a case study approach. The data collection techniques are by conducting interviews, observations, and documentation. The role of public relations in building the image of the external stakeholder company is to establish harmonious relations with the public using HKInsider, mass media, social media, positive news, and websites. In addition, maintaining communication with media partners and implementing Environmental Social Responsibility programs. In general, the role of Corporate Communication of PT Hutama Karya Infrastruktur answers research questions with the Excellence of PR theory by Grunig, Grunig. However, the basic part of the theory which states that public relations companies participate in decision making is not fulfilled in the function of HKI's public relations. Other important things are through social media, digital, and printing information to the public and stakeholders, building narratives with related parties, company public relations also negotiating with stakeholders to build mutually fostering and good relations. The main objective of all the efforts made is to create a good corporate image. Keywords: Role, Corporate Communication, Image, Stakeholder